Screening and Characterization of Aspergillus sp. KB2 for Decolorize Reed Dye - จันทมาลี จิรภัทร; อุณหศิริกุล มธุรา; คำฉัตร ณมนรัก; ปกาสิทธิ์ กมลชนก (KKU Science Journal, 2015)
Wastewater generated from reed mat production contains the high amount of exhausted dyes and pigments. This research aimed to isolate and characterize a fungal strain capable of decolorizing reed dye from soils and effluents collected from the manufacturing areas in Chanthaburi. A total of 19 indigenous fungal strains were obtained, but only nine of them could grow and produce a clear zone around the fungal colony culturing on red reed dye containing Czapek-Dox agar. After that, the dye removal efficiency of the selected strains was determined in Czapek-Dox broth containing 100 mg/l red dye. The treatments were incubated with shaking (80 rpm) at room temperature for 5 days. Isolate KB2, the most effective strain could reduce the color intensity at 87%. Therefore, KB2 was selected to test for its efficiency in reducing intensity of 100 mg/l mixed reed dyes (containing red, yellow, green and pink reed dyes in ratio of 1:1:1:1) and showed approximately 90% efficacy after 9 days incubation according to an increasing of cell mass. The identification results found that KB2 was belonged to genus Aspergillus by colony and cells morphological features. After that, the effect of reed dye concentration on KB2 biodegradation efficiency was determined. The treatments were incubated under the same conditions in C-limited Czaped-dox broth containing 50–500 mg/l mixed reed dyes. The results found that the high degradation efficiency ( 75%) was obtained when culturing Aspergillus sp. KB2 in 50 mg/l reed dye. As a result, this condition was used for immobilization of KB2 cells by adding 5 fungal discs into flasks containing immobilizing agents (5g dry weight) incubating at room temperature for 7 days. The results showed that the corncob - immobilized KB2 gave higher percentage (79%) of dye reduction compared to the zucchini fiberimmobilized KB2 (72%). In the future, this corncob-immobilized fungi may be used for decolorization of reed dyeing wastewater.